Daemonic ergotropy: enhanced work extraction from quantum correlations - Gianluca Francica (Nature Portfolio, 2017)
Quantum thermodynamics: Quantum correlations are key for work extraction! A strong connection exists between the ability of a quantum system to perform thermodynamic work and the amount of quantum correlations that are set in its physical configuration. Here, in this manuscript, the authors have considered the problem embodied by the extraction of thermodynamic work from an elementary quantum system. They have allowed the system to be aided by an ‘‘ancilla’’, upon which measurements can be performed in the best possible way. It has been found that more work is extracted from the system when it shares quantum correlations with its ancilla, thus shedding light on a fundamental question in quantum thermodynamics: are genuine quantum resources useful for thermodynamics purposes?